2020
DOI: 10.1152/physrev.00015.2019
|View full text |Cite
|
Sign up to set email alerts
|

Current Principles of Motor Control, with Special Reference to Vertebrate Locomotion

Abstract: The vertebrate control of locomotion involves all levels of the nervous system from cortex to the spinal cord. Here, we aim to cover all main aspects of this complex behavior, from the operation of the microcircuits in the spinal cord to the systems and behavioral levels and extend from mammalian locomotion to the basic undulatory movements of lamprey and fish. The cellular basis of propulsion represents the core of the control system, and it involves the spinal central pattern generator networks (CPGs) contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
418
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 383 publications
(429 citation statements)
references
References 477 publications
10
418
0
1
Order By: Relevance
“…In general, network oscillators (distinct from pacemaker or inhibition-based models) rely on recurrent excitation among constituent rhythmogenic neurons (Grillner, 2006;Grillner and El Manira, 2020). Modifying the neuronal excitability influences the relative fraction of spontaneously active neurons in the network, and, for silent neurons, the proximity of baseline membrane potential to spike threshold.…”
Section: Burstlet Mechanism: Network Oscillator That Depends On Recurmentioning
confidence: 99%
“…In general, network oscillators (distinct from pacemaker or inhibition-based models) rely on recurrent excitation among constituent rhythmogenic neurons (Grillner, 2006;Grillner and El Manira, 2020). Modifying the neuronal excitability influences the relative fraction of spontaneously active neurons in the network, and, for silent neurons, the proximity of baseline membrane potential to spike threshold.…”
Section: Burstlet Mechanism: Network Oscillator That Depends On Recurmentioning
confidence: 99%
“…The general organization of the serotoninergic system in the lamprey is relatively well described and appears to share similarities with that of other vertebrates (Abalo et al, 2007;Antri, Cyr, Auclair, & Dubuc, 2006 for review see Grillner, 2006;Grillner & El Manira, 2019). In this control, mainly postsynaptic 5-HT 1A Rs appear to be involved (e.g.…”
Section: Introductionmentioning
confidence: 96%
“…In healthy subjects, TMS over the primary motor cortex inhibits the CPQ reflex during locomotion (Iglesias et al, 2008a), and the cortical contribution to quadriceps activity during walking is weak compared to a more volitional movement like an isolated tonic contraction of quadriceps (Iglesias et al, 2012). Thus, it has been suggested that the control of quadriceps during stabilized locomotion is likely subcortical in origin, and the propriospinal system plays a significant role in the transmission of the motor command to motoneurons, in line with the role of midbrain structures in the control of spinal locomotor central pattern generators (CPGs) in vertebrates (Grillner and El Manira, 2019). Alternatively, the role of proprioceptive feedback, especially muscle spindle group II afferents that are particularly active during TA lengthening contraction at the beginning of stance, has been raised (Marchand-Pauvert and Nielsen, 2002).…”
Section: Possible Mechanisms Underlying the Music-induced Neuromodulamentioning
confidence: 99%
“…It has been well-established that listening to music and its practice induce remodeling of brain structures, with reorganization of neural networks in both healthy subjects and stroke patients (AltenmĂŒller and Schlaug, 2015;O'Kelly et al, 2016). Regarding the spinal cord, which is particularly involved in the control of locomotion (Grillner and El Manira, 2019), the effect of sound on spinal activity has started to be explored at the beginning of the 20th century. In 1914, Forbes and Sherrington have observed a facilitating effect of sound on the Hoffmann (H) reflex in decerebrate cats (Barnes and Thomas, 1968).…”
Section: Introductionmentioning
confidence: 99%